Factors Affecting Nonmarital Pregnancy in Teenagers at Soe City Public Health Center Work Area, Soe City Sud-District, South Mid-East Regency - Dwi Ertiana; Medrina Sofia Nakamnanu (STIKes Patria Husada Blitar, 2020)
Teen pregnancy is an international phenomenon that has not been resolved until now. Free sex behavior is an effect of out of wedlock pregnancy. The purpose of this research is what factors that affect out of wedlock nonmarital pregnancy on the teenager in the working area of Soe city public health center, South Central Timor regency. This research used descriptive quantitative research design, factors that affect out of wedlock pregnancy on teenager as a variable and 127 total population and simple random sampling used as a technique with 55 respondents. This research was conducted on 29-11 June 2019, in the work area of Soe city public health center, South Central Timor Regency. Research instrument used a questionnaire and data analysis used distribution of frequency percentage. The results showed that, 32 respondent (59%) were lack of knowledge, 35 respondent (64%) were influencing promiscuity, 31 respondents (57%) were more permissive to peer group norms, 35 respondents (64%) were parenting support while 21 respondent (38%) were technology and social media affect. This indicated that the most influential factor out of wedlock nonmarital pregnancy on teenager were individual factor that the teenager were lack of knowledge about reproductive health and sexuality, behavior factor that the teenager influenced by promiscuity, and environmental factor that parenting issue.